The Associations between Parental Conflict, Attachment Anxiety, and Somatic Symptoms in Adult Children Affected by Parental Separation. Issue 3 (2nd April 2020) - Lin, Hung-Chu; Yang, Yang; Elliott, Luke; Green, Eric
ABSTRACT: Using a sample of 210 college students affected by parental separation, this study investigated how perceived parental conflict and attachment anxiety jointly predicted somatic symptoms in adult children affected by parental separation. The participants responded to a computer-based survey assessing perceived parental conflict, attachment anxiety, and somatic symptoms. The results indicated that parental conflict was associated with attachment anxiety and somatic symptoms, and attachment anxiety was associated with somatic symptoms. Moreover, multivariate regression analysis showed a pattern of full mediation suggesting a pathway from parental conflict to somatic symptoms through the individual differences in attachment anxiety. Targeting anxious working models of attachment in children of parental separation may protect and minimize the vulnerability of developing somatic symptoms resulting from exposure to parental conflict.